STRATEGI PEMERINTAH KABUPATEN KOLAKA DALAM PENGUATAN TATA KELOLA PROGRAM CORPORATE SOCIAL RESPONSIBILYTY (CSR) - ABDUL SABARUDDIN; La Ode Muhammad Elwan; Maulid (Journal Publicuho, 2025)
This study aims to analyse the strategy employed by the Kolaka Regency Government in strengthening the governance of the Corporate Social Responsibility (CSR) program. The research utilises a qualitative approach, with data collection techniques that include in-depth interviews with key informants, regional policy documentation analysis, and a literature review. The findings indicate that the Kolaka Regency Government plays a pivotal role in policy formulation, facilitating cross-sector coordination, and overseeing CSR programs. Strategies implemented include the establishment of a Corporate Social and Environmental Responsibility (CSR) forum, which serves as a platform for collaboration among government entities, businesses, communities, and academic institutions. However, challenges persist, including a limited understanding of CSR implementation, suboptimal coordination efforts, and institutional constraints. The conclusion of this study underscores the necessity of enhancing local regulations, improving institutional capacity, and fostering sustainable partnerships as strategic measures to ensure the effectiveness and sustainability of CSR governance in Kolaka Regency.